Recurrent hypoglycaemia in a patient with thyrotoxicosis due to Insulin autoimmune syndrome - S. Sureshkumar; W. W. L. A. Jayanaga; R. B. A. T. Dulanjalie; S. A. P. N. Samarasingha; H. Karunathilaka (Sri Lanka College of Internal Medicine, 2023)
Insulin autoimmune syndrome (IAS) is an immune-mediated hyperinsulinaemic hypoglycemia in individuals previously unexposed to exogenous insulin. A 63-year-old woman developed recurrent hypoglycemic episodes despite being on optimal glycemic support. She was diagnosed with Graves' disease and was on carbimazole. Her insulin: C peptide ratio was suggestive of exogenous insulin administration or presence of insulin autoantibodies. Her insulin antibody level was elevated. IAS was probably secondary to her carbimazole therapy.